The use of urinary kidney injury molecule-1 and neutrophil gelatinase-associated lipocalin for diagnosis of hepato-renal syndrome in advanced cirrhotic patients - Mohamed Adel Abd Elaziz; Asmaa Mustafa Gouda Elewa; Dina Zaki Mohamed Zaki Abdel Hamid; Nohier Essam Soliman Ahmed Hassan; Éva Csongrádi; Emad Hamdy Hamouda Mohammed; Mohammed Abdel Gawad (Renal Failure)
Background Chronic liver disease is a common and important clinical problem. Hepatorenal syndrome (HRS) is a life threatening complication. Serum creatinine (Cr) remains the only conventional indicator of renal function. However, the interpretation of serum Cr level can be confounded by malnutrition and reduced muscle mass often observed in patients with severe liver disease. Here, we present a cross-sectional study to explore the sensitivity and specificity of other markers as urinary KIM-1 and NGAL for cases of HRS.Methods Cross-sectional study was conducted on 88 patients who were admitted to Alexandria main university hospital. Enrolled patients were divided in two groups; group 1: patients with advanced liver cirrhosis (child B and C) who have normal kidney functions while group 2: patients who developed HRS. Stata© version 14.2 software package was used for analysis.Results Group 1 included 18 males and 26 females compared to 25 males and 19 females in group 2 (p = 0.135). Only the urinary KIM-1 showed a statistically significant difference between both groups in the multivariate logistic regression analysis adjusted for gender, serum bilirubin, serum albumin, INR, serum K, AST and ALT levels.Conclusion In conclusion, our study aligns with prior research, as seen in the consistent findings regarding Urinary NGAL elevation in cirrhotic patients with AKI. Urinary KIM-1, independent of Urinary NGAL, may have a role in precisely distinguishing between advanced liver cirrhosis and HRS and merits further exploration.